Introduction to psychoanalysis contemporary theory and practice - Bateman, Anthony 1952-; Holmes, Jeremy 1943-; Allison, Elizabeth (Routledge, Taylor & Francis, 2022)
What is psychoanalysis? Is it relevant to today’s mental health crisis? How can psychoanalysis help people suffering from psychological distress and illness? This vital new book examines how psychoanalysis has changed since its inception, and how it has adapted to the needs and concerns of twenty-first century mental health professionals and patients.The first part of this book provides a concise and unbiased account of the origins of psychoanalysis, and the theories which characterize the main post-Freudian schools – neo-Freudian, Kleinian, Interpersonal, Self-Psychological, Lacanian – and the ways in which they agree and diverge. The second part uses clinical illustrations to examine the practicalities of psychoanalytic technique in the consulting room – assessment, free association, dream analysis, transference and counter-transference. Whatever their allegiance or role, mental health professions – psychologists, psychiatrists, social workers, child mental health professionals, mental health nurses – need to be conversant with the strengths, relevance, and limitations of the psychoanalytic approach.This book provides an indispensable, up-to-date and accessible account of psychoanalysis today. Shaped throughout by considering the viewpoint of an interested twenty-first century reader, it is of great interest to psychoanalysts and related mental health professionals, as well as students and all those interested in the treatment of mental health
Keywords: Psychoanalyse